Pengaruh Perceived Quality dan Perceived Value terhadap Brand Loyalty melalui Customer Satisfaction J-Klin Beauty Jember - Anton Yuliansyah; Timotius Dwi Handoko (COSTING : Journal of Economic, Business and Accounting, 2019)
Consumers play a very important role in providing an assessment of the quality of services obtained from service companies. This study aims to determine the effect of variable perceived quality and perceived value on the formation of brand loyalty through customer satisfaction of J-Klin customers in Jember Beauty Data used in this study is primary data. Data processing method uses path analysis method with the help of SPSS 24 analysis tool. The results of the study show that variable perceived quality and perceived value and customer satisfaction affect the formation of brand loyalty in J-Klin Beauty Jember customers either directly or indirectly Keywords: Perceived Quality, Perceived Value, Customer Satisfaction, Brand Loyalty